Visibility Issues of Right-Hand Drive Vehicles on the Right-Side Traffic - ŽURAULIS, Vidas; PEČELIŪNAS, Robertas; DROŹDZIEL, Paweł; PUKALSKAS, Saugirdas (Promet - Traffic&Transportation, 2026)
This paper analyses road safety issues related to the operation of right-hand drive vehicles in right-side operated traffic conditions. The problem is statistically valid, especially in regions where the states border with road traffic organised on different sides, or due to economic considerations, when it is much cheaper to purchase a vehicle adapted to the traffic of the other side. This article focuses on visibility issues of different driving positions in the case of the most dangerous overtaking manoeuvre by geometrically based situation analysis and safe distance to opposite obstacle evaluation. An additional part of the study is the functional testing of special indirect vision equipment in real traffic conditions. This is related to the technical regulations in force in the European Union Member States for vehicles adapted to the traffic in the other direction when constantly participating in traffic. An overview of these technical requirements, as well as the existing requirements not to restrict the free market of vehicles, is also covered in the paper.